Seasonal Variations of Sediment Fungal Community of a Shallow Lake in North China - Yujun Yi; Senlu Yin (Microorganisms)
Fungi play important roles in the process of material cycling and energy transfers in aquatic ecosystems. Yet, little is known about the fungal community in lake sediment. In this study, sediment samples from five habitat types in Baiyangdian Lake (BYD Lake) were collected across three seasons. High-throughput sequencing techniques were used to determine the compositions of fungal communities. Fungi are highly diverse in the sediment of BYD Lake, although some important fungi have not been accurately identified. The fungal diversity was highest in winter and lowest in summer, while there was no significant difference in species richness among sampling sites. The compositions of fungal community differed among seasons and habitats. Physicochemical properties of sediments were measured and the influence of the environmental factors on fungal communities were analyzed. Temperature, P, N, and heavy metals explained 48.98% of the variations of fungal communities across three seasons. Human activities have affected the species and biomass of fungi to some extent. Temperature is the most influential factor and negatively correlated to fungal diversity. Nutrients in different forms have different effects on shaping the fungal community. The effect of heavy metals is relatively low.